GE_GERICHTE C/18402/2014 vom 20. Februar 2015 - GE Cour de justice (2015)
CONVENTION BILATÉRALE(RECONNAISSANCE ET EXÉCUTION DES JUGEMENTS); CONVENTION DE LUGANO | LP.271.3; CL1988.26.1; CL1988.27; CL1988.28; CL2007.34; CL2007.35; CL2007.33.1